Changes in Maternal Psychophysiology Occurring in Response to Peer-Delivered Cognitive Behavioral Therapy for Postpartum Depression - Karunagoda, Tarindhya (My University, 2021)
Background: Postpartum Depression (PPD) affects up to one in five mothers. While psychotherapy can effectively reduce symptoms of PPD, it is unclear how PPD treatment affects maternal psychophysiology. Determining physiological changes in response to cognitive behavioural therapy (CBT) could provide insights into the mechanisms underlying effective treatment and/or help predict treatment outcomes. This study examined if treating PPD with CBT led to changes in frontal cortical activity and heart rate variability, two markers of maternal emotion regulatory capacity. Methods: Community-dwelling mothers with PPD (Edinburgh Postnatal Depression Scores ≥10) were randomized to receive nine weeks of group CBT delivered by recovered peers (i.e., those who had previously recovered from PPD) (n=26) or be put on a waitlist to receive the intervention nine weeks later (n=24). Electroencephalographic (frontal alpha asymmetry), electrocardiographic (heart rate variability), and clinical (depression, anxiety) data were collected at baseline and nine weeks later. Results: Participants in both the immediate treatment and waitlist control groups reported moderate levels of depression and anxiety at baseline. After treatment, mothers in the treatment group showed greater improvements in depression (p<0.01, Cohen d=1.22), and anxiety (p<0.005, Cohen d = 1.48), and high-frequency heart rate variability (p<0.05, Cohen d=0.70), but not frontal alpha asymmetry, compared to the waitlist control group. Conclusion: Group CBT for PPD can improve symptoms of depression and anxiety and parasympathetic nervous system function. Future research should attempt to replicate and extend these findings using larger samples, additional biomarkers, and longer periods of follow up. Examining how evidence-based treatments for PPD affect maternal psychophysiology can improve our understanding and potentially predict treatment effects.
Keywords: Postpartum depression, cognitive behavioural therapy, physiology, frontal alpha asymmetry, heart rate variability